Use of a Minimal Microbial Consortium to Determine the Origin of Kombucha Flavor - Tran, Thierry; Billet, Kevin; Torres-Cobos, Berta; Vichi, Stefania; Verdier, François; Martin, Antoine; Alexandre, Hervé; Grandvalet, Cosette; Tourdot-Maréchal, Raphaëlle (Frontiers in Microbiology, 2022)
Microbiological, chemical, and sensory analyses were coupled to understand the origins of kombucha organoleptic compounds and their implication in the flavor of the beverage. By isolating microorganisms from an original kombucha and comparing it to monocultures and cocultures of two yeasts (Brettanomyces bruxellensis and Hanseniaspora valbyensis) and an acetic acid bacterium (Acetobacter indonesiensis), interaction effects were investigated during the two phases of production. 32 volatile compounds identified and quantified by HS-SPME-GC/MS were classified according to their origin from tea or microorganisms. Many esters were associated to H. valbyensis, while alcohols were associated to both yeasts, acetic acid to A. indonesiensis and saturated fatty acids to all microorganisms. Concentration of metabolites were dependent on microbial activity, yeast composition, and phase of production. Sensory analysis showed that tea type influenced the olfactive perception, although microbial composition remained the strongest factor. Association of B. bruxellensis and A. indonesiensis induced characteristic apple juice aroma.